Unilateral high division of brachial artery and its clinical significance - Rohilla, Aarti; Parmar, Priyanka; Singh, Kamal; Rohilla, Jyoti (International Journal of Research in Medical Sciences, 2016)
Upper limb arterial variations are commonly encountered and have been reported in many articles. The present study showed a high division of brachial artery in the middle third of arm into its terminal branches, the radial artery laterally and the ulnar artery medially. This study is an attempt to discuss the anatomy, embryological basis and clinical implications of such variations. Knowledge of such anomalous vessels is significant from clinical point of view.